A New Superabsorbent Polymer Derived from Acrylamide and Fine Coal - Khotib, Mohammad; Mas'ud, Zainal Alim; Eriza, Nurul; Subastiar, Ian; Nasrudin, M Fikry (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
The fine coal was a by-product of the mechanical coal processing used at the coal mine, that can be converted to added value materials. The objective of this study to obtain the new superabsorbent polymers (SAP) derived from fine coal. The SAP synthesis was conducted via a free radical polymerization with various percentage of fine coal is 10; 25; and 40% of acrylamide and fine coal total. The copolymerization was carried out for 3 h at 70 C, followed by subsequent saponification with 1 M NaOH for 2 h. The superabsorbent composite was characterized by Fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). FTIR spectra revealed that the acrylic acid was successfully grafted onto the fine coal backbone. As shown by SEM imaging, the resulting surface was homogeneous and exhibited an interconnected pore structure. The maximum absorption capacity was found for SAP C2, which had a composition of 25% fine coal, 75% acrylamide, 0.11% N,N-methylene-bis-acrylamide (MBA), and 1.11% ammonium persulfate. The absorption capacities for the unsaponified and saponified SAPs were 42.36 and 617.86 g/g, respectively. The maximum water absorption capacity of the superabsorbent polymer was achieved at pH 6.5. Based on water absorption capacity, this product is suitable for soil conditioner or agricultural application.